2018
DOI: 10.1002/hep.29599
|View full text |Cite
|
Sign up to set email alerts
|

Systemic regulation of bilirubin homeostasis

Abstract: Neurotoxic bilirubin is the end product of heme catabolism in mammals. Bilirubin is solely conjugated by uridine diphospho-glucuronosyltransferase 1A1, which is a membrane-bound enzyme that catalyzes the transfer of glucuronic acid. Due to low function of hepatic and intestinal uridine diphospho-glucuronosyltransferase 1A1 during the neonatal period, human neonates develop mild to severe physiological hyperbilirubinemia. Accumulation of bilirubin in the brain leads to the onset of irreversible brain damage, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 78 publications
1
60
0
2
Order By: Relevance
“…Bilirubin conjugation increases water solubility and reduces cytotoxicity of bilirubin. Hepatic and intestinal UGT1A1 are functionally reduced in neonatal stages, and hence, unconjugated hyperbilirubinemia is commonly found in human neonates [ 2 ]. Conjugated bilirubin, or direct bilirubin, is the major form of bilirubin in bile and is eliminated in stool.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilirubin conjugation increases water solubility and reduces cytotoxicity of bilirubin. Hepatic and intestinal UGT1A1 are functionally reduced in neonatal stages, and hence, unconjugated hyperbilirubinemia is commonly found in human neonates [ 2 ]. Conjugated bilirubin, or direct bilirubin, is the major form of bilirubin in bile and is eliminated in stool.…”
Section: Main Textmentioning
confidence: 99%
“…Jaundice, a yellowish pigmentation of the skin and sclera, is caused by the disrupted excretion of bilirubin and biliverdin. Interestingly, some studies involving neonates or adults have shown that hyperbilirubinemia is protective against diseases, including metabolic syndrome and asthma, [ 2 , 3 ] suggesting that bilirubin may play a role as an antioxidant [ 4 ].…”
Section: Main Textmentioning
confidence: 99%
“…In clinical settings, an increase in bilirubin may indicate amongst others haemolysis, liver failure, or obstruction of the biliopancreatic system. 18 A possible explanation for the present phenomenon might be increased transport capacity of unconjugated bilirubin by increased intravascular albumin concentration. 19 The authors of the Albumin Replacement in Patients with Severe Sepsis or Septic Shock (ALBIOS) trial also detected an increase in serum bilirubin concentration in patients receiving intravenous albumin and considered relevant amounts of bilirubin in the administered albumin solutions as a potential reason.…”
Section: Discussionmentioning
confidence: 79%
“…Although UGT1A1 is the sole enzyme responsible for the glucuronidation of bilirubin in humans, low UGT1A1 activity is not the sole risk factor for the development of Gilbert's syndrome . Indeed, in addition to defective bilirubin conjugation (low UGT1A1 activity), such as defective bilirubin uptake by hepatocytes (eg, polymorphisms in the organic anion transporting polypeptide 2, defective heme oxygenases, defective biliverdin reductase A, G6PD deficiency, and breast feeding) are also risk factors for the development of unconjugated hyperbilirubinemia . Those risk factors are worthy of investigation in patients suffering from hyperbilirubinemia with low to moderate UGT1A1 activity (>41% of normal).…”
Section: Discussionmentioning
confidence: 99%